The Role of Technology and Social Media in Spreading the Qur'an and Hadiths by Mubalig - Hidayaturrahman, Mohammad; Putra, D.I Ansusa (IAIN Surakarta, 2019)
This research was conducted to find out how the role of technology and social media in spreading Al-Quran and hadith by the mubalig. This research uses qualitative descriptive approach, while the method of collecting data with observation on the activities of the mubalig and dai who perform religious da’wa activities, both in mosques, langgar, and majlis taklim assemblies held at homes of pilgrims or mubalig house. This research found that, mubalig already flat using technology and social media for the purposes of their da’wah. The preachers use technology and social media for various purposes of da’wa, communicating with the congregation of recitation, to read references of religious material, as well as as a means to store the propagation material which subsequently submitted during the recitation. The last is to make existing apps their devices to recall verses or hadiths that happen to be forgotten when delivering lecture material. The mubalig rate, technology and social media are something positive to use as a medium of communication preaching. So that mubalig are not allergic to technology and social media, even some of them become active users in social media. Similarly, in his own devices there are many applications of the Qur'an and Hadith. Carrying a device is an effective way of learning, carrying the reference of the book, because it does not have to bring a large book of physical to come preach to various places and locations. Technology is considered to be able to connect them with the other ustaz, kiai or religious figures in the same or different organization.